Effect of entomopathogenic fungi introduced as corn endophytes on the development, reproduction, and food preference of the invasive fall armyworm Spodoptera frugiperda - Russo, Maria L. (2020)
Fall armyworm (FAW), Spodoptera frugiperda, is a migratory polyphagous pest that causes major damage to economically important cultivated grasses, such as corn. Native to the neotropics in America but recently reported as an invasive pest in Africa and Asia, FAW imposes a serious threat to food security and sustainable crop productivity due to lack of efective management. In this study, the introduction of entomopathogenic fungi as endophytes was explored as an alternative more sustainable management strategy against FAW in corn. The study determined (1) the efect of isolates and inoculation methods on the ability of entomopathogenic fungi to colonize corn plants, and (2) the efect of colonized plants on S. frugiperda survival, development, reproduction, and food preference. Although all tested isolates (twelve of Beauveria bassiana and one each of Metarhizium anisopliae and Metarhizium robertsii) colonized inoculated plants, there was a highly signifcant interaction between isolates and inoculation methods. Highest plant colonization was obtained by Beauveria bassiana isolate (LPSc 1098) using foliar spray. Endophytic B. bassiana caused signifcant reductions in larval and pupal survival, length of diferent developmental stages, total S. frugiperda lifespan, and leaf area consumed by third instar larvae. Plant colonization also signifcantly reduced female longevity, fecundity, and fertility. This is the frst report for the negative efects of endophytic B. bassiana on S. frugiperda growth, reproduction, and food preference. Our results highlight the promising potential of incorporating entomopathogenic fungi as endophytes in integrated pest management practices to protect corn against FAW if their efcacy is also confrmed under feld conditions.